Editorial Board and Table of Contents (Relevant Tomorrow / Aktualu rytoj, 2024)
Special Issue “Monadological Landscapes: Reflections of Leibniz’s Theory in Philosophy and Painting”Special Issue Editor Kristijona Čerapaitė